2020
DOI: 10.1080/14786419.2020.1797725
|View full text |Cite
|
Sign up to set email alerts
|

New phytoconstituents, anti-microbial and cytotoxic activities of Acacia etbaica Schweinf

Abstract: Acacia etbaica is wild plant growing in the desert of Egypt, and it has folkloric medicinal uses. Phytochemical investigation of Acacia etbaica extracts led to the isolation and identification of seven compounds. Among these compounds are three new simple phenolics: Resacetophenone-6-methyl [1], Resorcinol [2], Resorcinol-O-β -Glucoside [3]; phenolic ester; and other four known compounds: Methylparaben [4]; two chromones, Noreugenin [5], Eugenin [6]; and one cyclitol: pinitol [7]. Compounds [1-3] isolated and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The compound ( 4) is D-pinnitol (yellow amorphous solid). NMR ( 1 H, 13 C(APT)) (400 MHz, (CD 3 OD) Spectral data in Table 3 are consistent with those reported in the literature [36][37] .…”
Section: Compound (4)supporting
confidence: 88%
“…The compound ( 4) is D-pinnitol (yellow amorphous solid). NMR ( 1 H, 13 C(APT)) (400 MHz, (CD 3 OD) Spectral data in Table 3 are consistent with those reported in the literature [36][37] .…”
Section: Compound (4)supporting
confidence: 88%
“…The UV absorption bands at 213, 270, 349 nm suggested that compound 4 is a flavone derivative [8] . The 1 H‐NMR spectrum obtained at 400 MHz in (D 6 )DMSO displayed a singlet at δ H 12.80 ppm (1H, s, 5‐OH) attributed to a hydroxy group presenting an intramolecular hydrogen‐band with the carbonyl group [9] . It shows also three signals at δ H 7.53 ppm (1H,d, J =2.4 Hz), δ H 6.88 ppm (1H,d, J =8.4 Hz) and δ H 7.67 ppm (1H,dd, J =8.4 Hz, 2.4 Hz) corresponding to one 1,3,4 tri‐substituted aromatic ring as well as one singlet attributed to an olefinic proton at δ H 6.70 ppm (1H, s).…”
Section: Resultsmentioning
confidence: 99%
“…[8] The 1 H-NMR spectrum obtained at 400 MHz in (D 6 )DMSO displayed a singlet at δ H 12.80 ppm (1H, s, 5-OH) attributed to a hydroxy group presenting an intramolecular hydrogen-band with the carbonyl group. [9] It shows also three signals at δ H 7.53 ppm (1H,d, J = 2.4 Hz), δ H 6.88 ppm (1H,d, J = 8.4 Hz) and δ H 7.67 ppm (1H,dd, J = 8.4 Hz, 2.4 Hz) corresponding to one 1,3,4 tri-substituted aromatic ring as well as one singlet attributed to an olefinic proton at δ H 6.70 ppm (1H, s). In addition, the presence of an isolated aromatic proton at δ H 6.28 ppm (1H, s) indicated a pentasubstituted aromatic ring.…”
Section: Extraction and Isolationmentioning
confidence: 99%
“…Quantification of the compound in both crude extracts by qNMR revealed that it was significantly more abundant in the leaves with 64.83±0.88 mg g −1 DW compared to the stems where 24.89±0.06 mg g −1 DW was observed (Figure 4). Pinitol has previously been identified in Vachellia species including V. nilotica , [13] V. farnesiana , [14] and V. etbaica Schweinf [15] . as well as several Acacia species [9–10] .…”
Section: Resultsmentioning
confidence: 99%
“…Pinitol has previously been identified in Vachellia species including V. nilotica, [13] V. farnesiana, [14] and V. etbaica Schweinf. [15] as well as several Acacia species. [9][10] In addition to various pharmacological effects including hepatoprotective, anticancer, cardioprotective and anti-inflammatory effects, several studies have reported the anti-diabetic properties of the compound.…”
Section: Major Compounds and Differences Between The Leaf And Stem Pr...mentioning
confidence: 99%